2013
DOI: 10.1016/j.jtcvs.2012.07.100
|View full text |Cite
|
Sign up to set email alerts
|

Mild-to-moderate functional tricuspid regurgitation in patients undergoing mitral valve surgery

Abstract: Early or late clinical benefits of concomitant TV repair for mild-to-moderate TR during mitral valve surgery were uncertain through a long-term follow-up of 959 patients. Several preoperative factors and the performance of Maze procedure for AF seem to be more important than TV repair in overall clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 15 publications
(13 reference statements)
2
27
0
5
Order By: Relevance
“…TR is also associated with increased late postoperative morbidity and mortality. [2][3][4][5][6][7] The timing of tricuspid valve surgery is important because patients with TR have anemia, organ dysfunction, and right ventricular (RV) dilatation, which also are associated with poor surgical outcomes. 8 Structural heart changes in severe TR are well described and include tricuspid annular dilation and RV and right atrial (RA) enlargement.…”
mentioning
confidence: 99%
“…TR is also associated with increased late postoperative morbidity and mortality. [2][3][4][5][6][7] The timing of tricuspid valve surgery is important because patients with TR have anemia, organ dysfunction, and right ventricular (RV) dilatation, which also are associated with poor surgical outcomes. 8 Structural heart changes in severe TR are well described and include tricuspid annular dilation and RV and right atrial (RA) enlargement.…”
mentioning
confidence: 99%
“…Nowadays, the increased need for TA is due to the aggressive approach chosen by the surgeons. According to the literature, 2,5,11,19 in most cases functional TR is not reduced after treatment of MV disease, but, after an early downgrading, it slowly increases again. Hence, surgery is indicated in patients with severe TR and should be considered in patients with mild or moderate TR with a tricuspid annulus ≥40 mm 3,4,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Since Dreyfus et al 2 demonstrated that TR may further impair even after successful mitral valve (MV) surgery, most surgeons started to treat less than severe TR in the presence of a dilated annulus (>40 mm or >21 mm/m 2 ) 3,4 . However, the results of tricuspid annuloplasty (TA) still flawed, hence prophylactic TA remains underused, 5 performed only in 10% of patients with MV disease 6…”
Section: Introductionmentioning
confidence: 99%
“…The observation that FTR could progress after successful MV replacement or repair was paramount to force surgeons to correct even less than severe FTR in the presence of a dilated annulus (>40 mm or >21 mm/m²). The results of surgical correction are, however, still flawed, and prophylactic tricuspid annuloplasty (TAP) remains controversial and underused, being performed only in 10% of patients with MV disease…”
Section: Introductionmentioning
confidence: 99%